Bilateral coupling relationships between vegetation NDVI and multi-depth soil moisture in the Mongolian Plateau - Shubo Zhang; Siqin Tong; Jinyuan Ren; Gang Bao; Xiaojun Huang; Yuhai Bao; Dorjsuren Altantuya (International Journal of Digital Earth, 2025)
Soil moisture governs vegetation growth and distribution, which in turn affects its dynamics through transpiration, interception, root water uptake, and soil structure improvement. Understanding these interactions is vital for effective ecosystem management and sustainable development. This study analyzes the interactions and lag effects between soil moisture at different depths and NDVI on the Mongolian Plateau from 1982–2022 using trend, correlation, and nonlinear Granger causality analyses. The results show that the significant increase in vegetation is accompanied by a notable decrease in soil moisture. Increased vegetation promotes shallow soil moisture retention but accelerates deep soil moisture depletion as drought intensifies, extending the lag time. Concurrently, while soil moisture generally positively affects NDVI, this relationship becomes negatively correlated in deeper layers. Overall, soil moisture had a causal relationship with NDVI in 65.7 to 76.9% of the areas, indicating broad influence by soil moisture. Conversely, vegetation exerted a regulatory effect on soil moisture in 38.9to 66.5% of the regions. As depth increased, bidirectional causality gradually weakened, transitioning to a unidirectional influence of soil moisture on NDVI. In arid regions, NDVI more significantly impacted deep soil moisture, highlighting the need for increased focus on vegetation's effect on water consumption.